The Illustrious Prince - Oppenheim, Edward Phillips (Saga Egmont, 2021)
Set in Britain shortly after the end of the Russo-Japanese war, ‘The Illustrious Prince’ provides a fascinating insight into the political tensions of the time. The story centres around Prince Maiyo – a cousin of the Emperor of Japan who has been dispatched to Britain in order to seek out a Western ally. Suspicion falls on Prince Maiyo following a daring murder however – which side is he really on?